The restructuring of WA human services and its implications for the not-for-profit sector - Fitzgerald, Scott; Rainnie, Alistair; Goods, Caleb; Morris, L. (Australian Council of Social Service, 2014)
Western Australia provides an interesting case study of the outsourcing of human services to the not-for-profit (NfP) sector. This article presents and discusses some of the key themes that emerged from a recently completed research project examining one large NfP in Western Australia. Key themes included the recruitment and retention of staff linked to pay and changing funding arrangements, and the sector becoming increasingly corporatised in outlook and goal orientaiton. Despite evidence that the shifting policy and funding environment within the NfP sector has had some negative consequences, the research findings highlight a degree of agency within which organisations can resist or counterbalance these changes. Efforts to avoid this trend, however, are reliant upon a number of factors; for example, a strong commitment to vision and mission supported by skilled leadership and adequate resourcing. Significantly, these factors are unlikely to be readily available, particularly for smaller NfPs. This discrepancy in organisational capacity is set to become more conspicuous with the potential introduction of ‘Big Society’ policies derived from the United Kingdom, and funding cuts proposed by the Coalition government.